PENGARUH PENAMBAHAN ENZIM PAPAIN DAN ENZIM BROMELIN TERHADAP HIDROLISAT PROTEIN DARI AMPAS KELAPA - Ridhwan, Alverdha Elvarheta Rasseta; Herdyastuti, Nuniek (Unesa Journal of Chemistry, 2024)
Coconut dregs waste has potential to be used as protein hydrolysate with addition of papain enzyme and bromelain enzyme. The study aimed to analyze the effect of enzyme concentration and hydrolysis time on coconut pulp protein hydrolysate based on yield, protein content, and degree of hydrolysis. The enzyme concentration used variations of 1, 3, 5, 6, and 7% (b/v) which were hydrolyzed for 240 minutes. Determination of protein content was done by Bradford method and measurement of hydrolysis degree by SN-TCA method. The results showed the best protein hydrolysate in addition of papain enzyme at 7% concentration with a yield of 24.70%, protein content of 0.03450 mg/mL, and degree of hydrolysis of 48.04%. These results were greater than addition of 7% concentration of bromelain enzyme with a yield of 18.46%, protein content of 0.03067 mg/mL, and degree of hydrolysis of 42.30%. The variation of hydrolysis time was 150, 180, 210, 240, and 270 minutes with 7% enzyme concentration for each enzyme. The results showed that the best hydrolysis time was 270 minutes with papain enzyme which produced 23.44% yield, 0.03550 mg/mL protein content, and 65.36% hydrolysis degree. These results are greater than the hydrolysis time of 270 minutes with bromelain enzyme producing a yield of 17.06%, protein content of 0.03360 mg/mL, and degree of hydrolysis of 50.20%. This study showed that protein hydrolysate with the addition of papain enzyme showed better results than the addition of bromelain enzyme.